Comparative Study of Antioxidant Activity of Buni Fruit Extract (Antidesma bunius (L.) Spreng.) Using Various Extraction Techniques - Hamdayani Lance Abidin; Abdul Halim Umar; Saldi Hapiwaty; Fhahri Mubarak; Asril Burhan; Sukriani Kursia; Maria Ulfa; Imrawati Imrawati (Journal of Health and Nutrition Research, 2026)
Buni fruit (Antidesma bunius L.) is a native Indonesian plant that contains anthocyanin, flavonoid, and phenolic compounds, so it has the potential as a source of natural antioxidants that are beneficial for health. This study aims to evaluate the antioxidant activity of extracts taken using various extraction methods because they can affect the results, composition of bioactive compounds, and the ability to scavenge free radicals. Buni fruit simplicia was extracted using 96% ethanol through three extraction techniques, namely maceration, soxhletation, and reflux. In vitro antioxidant activity testing was carried out using the DPPH method by determining the IC₅₀ value. The reflux method gave the highest yield (13.99%) when compared to maceration (9.42%) and soxhletation (12.60%). However, the extract from the maceration method had an IC₅₀ value (74.445 µg/mL) indicating the strongest antioxidant activity compared to soxhletation (155.104 µg/mL) and reflux (161.894 µg/mL). The results of one-way ANOVA analysis showed that the extraction method did not have a significant effect on the percentage of DPPH inhibition (p>0.05). This indicates that differences in extraction methods have not been able to produce statistically significant differences in antioxidant activity.